2014
DOI: 10.1093/pch/19.9.475
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of paediatric concussion among front-line primary care providers

Abstract: Considerable gaps in knowledge exist in front-line primary care providers with inadequate application of graduated return to play and return to learn following concussion, as demonstrated by the present broad population-based survey. Consistent application of best evidence-based management using comprehensive guidelines may help to reduce the impact of concussion and persistent postconcussive problems in children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 30 publications
6
45
0
Order By: Relevance
“…48 The authors' team carried out a similar study of family doctors, general emergency physicians, nurse practitioners, and general pediatricians practicing in Ontario and found that similar gaps in knowledge existed across all provider types. 49 …”
Section: Limitationsmentioning
confidence: 99%
“…48 The authors' team carried out a similar study of family doctors, general emergency physicians, nurse practitioners, and general pediatricians practicing in Ontario and found that similar gaps in knowledge existed across all provider types. 49 …”
Section: Limitationsmentioning
confidence: 99%
“…A recent study reported that among primary care physicians who manage patients with sport-related concussion, 70% reported using published guidelines when making clinical decisions related to concussion management. 18 In comparison, our study suggests that sports medicine physicians follow published guidelines at a higher rate than physicians of other specialties. Our data also suggest that sports medicine physicians seem to be aware of periodic updates to consensus guidelines, with almost 92% of respondents reporting use of most recent guidelines provided by the Fourth International Conference on Concussion.…”
Section: Discussionmentioning
confidence: 60%
“…However, our response rate is comparable with previous similar studies. 15,17,18 CONCLUSIONS Sports medicine physicians commonly use recently developed guidelines, balance assessments, neuropsychological tests, and medications when managing sport-related concussions. As concussion management evolves, additional…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, research has assessed concussion knowledge of stakeholders other than athletes, coaches, and parents. For instance, concussion knowledge of healthcare providers/clinicians (Zemek et al, 2014;Zemek et al, 2015), athletic trainers (Cusimano et al, 2009;Esquivel et al, 2013Naftel et al, 2014, physical therapists (Yorke, Littleton, & Alsalaheen, 2016), and speech-language pathologists (Duff & Stuck, 2015), has been examined. Such stakeholders may play pivotal roles in reducing and managing youth concussions.…”
Section: Discussionmentioning
confidence: 99%